ADR evaluation of screening colonoscopies during 2016 – 2017 in a private health clinic in Peru - León Moreno, Julio F. (Endoscopy International Open, 2018)
Background and study aims High-quality colonoscopy is fundamental for preventing colorectal cancer (CRC). The adenoma detection rate (ADR) is a key colonoscopy quality measure. The aim of this study was to establish the screening colonoscopy ADR of a tertiary referral center in Peru, identify the relationship between the ADR and patient age, sex and the colonoscopist, and determine the endoscopic and histopathological characteristics of the lesions found.Patients and methods A retrospective observational longitudinal study was undertaken between January 2016 and June 2017. Results Eight colonoscopists performed screening colonoscopies on 620 patients scoring ≥ 6 points on the Boston Bowel Preparation Scale (BBPS); cecal intubation was complete in 595 patients (cecal intubation rate [CIR] 95.9 %). The overall ADR was 29.7 % (females 25.4 %, males 33.1 %, P = 0.040, 95 %Cl). The ADR colonoscopist range was 25.0 % to 34.4 %. The highest ADR (41.2 %, P = 0.013, 95 %Cl) was for patients aged 65 to 75 years. Adenoma colon locations were: left 49 %, transverse 21.6 % and right 29.4 %. Adenoma dysplasia grades: low 98 %, high 2 %. Sixty-three percent of the lesions were 5 mm to 10 mm. Resections performed: 78.5 % cold biopsy forceps (CBF), 3.4 % cold snare polypectomy (CSP) and 18.1 % endoscopic mucosal resection (EMR).Conclusions The ADR established was in line with the joint American College of Gastroenterology (ACG)/American Society for Gastrointestinal Endoscopy (ASGE) recommendations and related to patient age and gender but not to the colonoscopist. Colonoscopists should ensure rigorous application of the colonoscopy quality actions. ADR should be evaluated frequently.